Physical Dynamics of the Indian Ocean to Tropical Cyclone Neville (2024) - Ainur Rahmat Hidayah Ilham; Giri Dwi Kartika Ary (BIO Web of Conferences)
Wind stress induced by Tropical Cyclone (TC) can be a strong trigger for the occurrence of divergent and upwelling water mass movements and affect the physical dynamics of the ocean. This research is essential to understanding how the intensity TC affects the physical dynamics of the ocean by comparing three conditions, namely pre, during, and post TC Neville, so that it can reveal patterns of changes in the marine environment due to TC. Observations were made using a combination of Argo float and remote sensing data, to determine the vertical and horizontal physical dynamics in the region. The results showed that the strong Ekman pumping velocity around the cyclone track caused the cooling of the sea surface in the region and deepened the Mixed Layer Depth (MLD). In addition, along Pre-TC, the MLD was 0-12 m, nevertheless deepening the MLD was saw to 14 m (0-26 m) in Post-TC. We conclude that TC Neville can cause changes to the physical dynamics in the Indian Ocean, especially around the TC area.